Effect of enlarged adenoid in the development of otitis media with effusion under the Age of 12 - Barua, Raju; Tarafder, Kamrul Hassan; Rahman, Mohammad Wakilur; Md Jamil, Abu Naser; Haque, Farzana; Yesmin, Naseem (Bangladesh Journal of Otorhinolaryngology, 2020)
Objective: To find out relation between enlarged adenoid and otitis media with effusion (OME), degree of hearing loss in OME cases with the size of the adenoids and degree of pressure changes in middle ear in OME cases with the size of adenoids. Method: This Prospective Study was carried out Bangabandhu Sheikh Mujib Medical University, Shahbag, Dhaka and Specialized ENT Hospital of SAHIC, Mohakhali, Dhaka from September 2010 to March 2011 (7 months). Randomly selected 50 children (Age below 12 years) with enlarged adenoid in outdoor & indoor. Patient with sensorineural hearing loss and conductive hearing loss with other than enlarged Adenoids are exclude in this study. Result: In this study, 58% had hearing loss in which 38% were mild and 20% were moderate loss. 54% of ears had negative pressure. 22 cases of severe adenoids of which 72.72% had OME.10 out of 16 OME with severe adenoids cases having hearing loss were in 26-40 db range and middle ear pressure is -201 to -400 dapa. Conclusion: Early diagnosis and treatment of enlarged adenoids should be aparciated to decrease the incidence, morbidity and complications of otitis media with effusion. Bangladesh J Otorhinolaryngol; April 2016; 22(1): 48-52